Rasio Legis Pertimbangan Hakim Dalam Putusan Perkara Narkotika (Nomor 219/PID.SUS/2019/PN.GTO Dan Nomor 263/PID.SUS/2019/PN.GTO) - Suci Nabila Mustapa; Fence M. Wantu; Julisa Aprilia Kaluku (Lembaga Pengembangan Kinerja Dosen, 2024)
The criminal disparity is inconsistent of different decisions toward crime with similar characteristics where its danger is comporable without obvious justification. Narcotics are substances or drugs from plants or others, wheter synthetic or semi synthetic, that can fatally affect the consciousness and lead to an addiction. This study aimed to analyze the factors influencing the disparity in judges decisions and the solutions or judges consideration in sentencing toward drug abuse cases. This normative research used a case approach referencing primary, secondary, and tertiary legal materials. Data collection techniques were carried out using literature studies. Based on the analysis, two factors influenced the judges decision legal and social. Besides, the verdict made by the judge has not fulfilled the sense of justice due to the irrelevancy.